Pengaruh Tehnik Marmet terhadap Kelancaran Asi pada Ibu Postpartum di Puskesmas Sei Berombang Kecamatan Panai Hilir - Irmawati Irmawati; Rotua Lenawati Tindaon; Haswani Haswani; Haziyah Haziyah (Universitas Malahayati Lampung, 2023)
ABSTRACT Breast milk (ASI) is the best food for babies because it contains all the nutrients that babies need and protective substances from various germs. The purpose of this study was to determine the effect of the marmet technique on the smoothness of breastfeeding in postpartum mothers at the Sei Berombang Health Center, Panai Hilir District. This type of research is a quasi-experimental design with one group pretest-posttest design. The population of this study was postpartum mothers on the 2nd day using a total sampling technique with a total sample of 16 postpartum mothers. The results of this study used the Wilcoxon test. Based on the Wilcoxon test, the p-value was 0.000 (0.05), meaning that there was an effect of the marmet technique on the smoothness of breastfeeding in postpartum mothers. The conclusion of this study is that there is an effect of the marmet technique on the smoothness of breast milk in postpartum mothers and it can be applied to accelerate the release of breast milk, milk production and smooth breast milk. Suggestions from this study are expected that the marmet technique process can be used as an alternative in accelerating breastfeeding so that breastfeeding becomes smooth and exclusive breastfeeding can be carried out. Keywords: Marmet Technique, Smooth Breastfeeding, Postpartum ABSTRAK Air susu ibu (ASI) merupakan makanan yang terbaik untuk bayi karena mengandung semua nutrisi yang dibutuhkan bayi dan zat pelindung dari berbagai kuman. Tujuan penelitian ini untuk mengetahui adanya pengaruh tehnik marmet terhadap kelancaran asi pada ibu postpartum di Puskesmas Sei Berombang Kecamatan Panai Hilir. Jenis penelitian ini adalah quasi eksperiment dengan desain one group pretest-posttest desain. Populasi dari penelitian ini adalah ibu postpartum hari ke2 menggunakan teknik total sampling dengan jumlah sampel 16 orang ibu postpartum. Hasil penelitian ini menggunakan uji wilcoxon. Berdasarkan uji wilcoxon didapatkan nilai p-value 0,000 ( 0,05), berarti ada pengaruh tehnik marmet terhadap kelancaran asi pada ibu postpartum. Kesimpulan dari penelitian ini yaitu ada pengaruh tehnik marmet terhadap kelancaran asi pada ibu postpartum dan dapat diaplikasikan untuk mempercepat pengeluaran ASI, produksi ASI dan kelancaran ASI. Saran dari penelitian ini diharapkan proses tehnik marmet dapat dijadikan alternatif dalam mempercepat pengeluaran ASI sehingga ASI menjadi lancar dan ASI eksklusif dapat terjalani. Kata Kunci: Tehnik Marmet, Kelancaran ASI, Postpartum